Conquering Basic Properties of Even Perfect Numbers Using the Gun of Finite Series - Shields, Nicquala; Lemma, Mulatu (IJRDO -JOURNAL OF MATHEMATICS, 2017)
Mathematicians have been fascinated for centuries by the properties and patterns ofnumbers. They have noticed that some numbers are equal to the sum of all of their factors (notincluding the number itself). Such numbers are called perfect numbers. Thus a positive integer iscalled a perfect number if it is equal to the sum of its proper positive divisors. The search forperfect numbers began in ancient times. The four perfect numbers 6, 28, 496, and 8128 seem tohave been known from ancient times. In this paper, we will investigate some important basicproperties of perfect numbers.